Potential of Organic Infusion as a Preferred Attractant for Mosquito Oviposition: A Literature Review - Saleh, Muh.; Basri, Syahrul; Ekasari, Ranti (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
This study reviews the potential of organic substances (organic infusion) as an attractant for oviposition of gravid mosquito trap in surveillance and control of the mosquito mosquito-borne disease based on literature indexed by Scopus and Web of Science (WOS), such as PubMed, ScienceDirect, MDPI, Springer, Wely, SiELO, and Cochrane Database of Systematic Reviews. A total of 1,804 scientific papers were obtained, and only 12 articles met the inclusion criteria. All selected articles were quantitative studies (laboratory, semifield, and field studies). The results showed that the Ae. aegypti, Ae. albopictus and various species of Culex are attracted to organic infusion. The organic infusion is effective in attracting mosquitoes to lay eggs in traps, especially Aedes spp. It can be used as surveillance and the best solution in environmentally friendly disease vector control.